Learning strategy of the lean manufacturing philosophy through the implementation of the LEGO® SERIOUS PLAY methodology - Fajardo Buitrago, Jonatan Arley
This research studies the application of the LEGO® SERIOUS PLAY® methodology in manufacturing processes in the training program for garment workers. Through a case study, the motivation and experience of the participant in the importance of improving processes from their workplace and the application of continuous improvement tools such as the five s, poka-yoke and the mitigation of the 7 lean wastes are evaluated. The Lego® Serious Play® methodology is based on the idea that through practice, participants can work as a team using their creativity and face work under pressure and decision making, strengthening individual and group commitment, in order to meet the objectives of manufacturing organizations to improve certain indicators such as productivity, efficiency, effectiveness, performance and others. Finally, information is transferred from the lean manufacturing philosophy with the objective of integrating improvement processes optimizing resources to avoid waste from overproduction, inventory, over processing, transportation, waiting, movements and reprocessing. The participants in the case study have the possibility to assemble a product from their creativity fulfilling certain requirements, through a linear production process the trainees will have to assemble the requested units in the time they calculate, in this way and through the implementation of lean tools will have the opportunity to balance the process to meet the objective and to make certain improvements found in the course of the exercise, teamwork and the identification of opportunities for improvement and implementation of the same will be the necessary resource to fulfill the activity.